Implementasi Dashboard Data untuk Analisis Penjualan PT Anugerah Bersama Bogor - Andika Agung Triadha; Farizi Ilham; Aryo Maulana Putra; Muhammad Azhar Rahmatullah (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
PT Anugerah Bersama Bogor is a company engaged in clean water distribution services using tanker truck fleets. The sales data management process is still conducted manually through phone calls, WhatsApp messages, and delivery reports, resulting in difficulties in transaction monitoring, delays in report generation, and limited data analysis for decision-making purposes. This study aims to implement a web-based data dashboard capable of presenting integrated, real-time, and easy-to-understand sales information. The research applied the Waterfall model of the System Development Life Cycle (SDLC), consisting of requirements analysis, system design, implementation, and testing phases. Data were collected through observation, interviews, and literature studies. The system was developed using the Laravel framework and MySQL database and provides features such as interactive data visualization, dynamic filtering, Key Performance Indicators (KPI), sales forecasting, report export, and scheduled data refresh. The implementation results indicate that the dashboard improves the efficiency of sales data management, accelerates reporting activities, facilitates real-time sales performance monitoring, and supports faster and more accurate managerial decision-making. Therefore, the proposed system can serve as an effective solution for enhancing sales information management within the company.